Pengembangan Potensi Mangrove sebagai Produk Pangan Fungsional di Kecamatan Wonorejo Surabaya - Yulistiani, Ratna; Finatsiyatull Rosida, Dedin; Savitri, Anggita; Meireni Zacharya, Berlianda (Universitas Nahdlatul Ulama Sidoarjo, 2023)
One of the coastal areas that has large areas of potential mangroves is Wonorejo District, East Surabaya. The Wonorejo Mangrove Ecotourism concept provides economic benefits for people who have creative small industries to improve people's living standards. Pedada fruit (Sonnerita spp) is one of the products of mangrove forests which is rich in nutritional content, rich in antioxidants and dietary fiber which has great potential to be developed as a functional food product. The UPN Veteran East Java community service program in the